The Impact of the Addition of Effective Microorganisms on Selected Parameters of Engine Oil - Rafał Krakowski (Scientific Journal of Gdynia Maritime University, 2023)
This article presents the problem of microbial contamination in petroleum products and describes in detail the presence of microorganisms and the methods currently used to combat microorganisms in lubricating oil. Effective microorganisms have also been characterised in terms of composition and development conditions. The main part of the article presents the effect of the ecological additive on selected parameters of engine oil. From the preliminary results obtained, it is to be concluded that these additives can be added instead of, for example, harmful biocides. Effective microorganisms have a positive effect on the properties of both new and used oil. Therefore, it is justified to conduct further studies for other oil parameters and for different amounts of this ecological additive.